2022
DOI: 10.1101/2022.12.14.22283419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Social Media to Help Understand Long COVID Patient Reported Health Outcomes: A Natural Language Processing Approach

Abstract: Background: There remains significant uncertainty in the definition of the long COVID disease, its expected clinical course, and its impact on daily functioning. Social media platforms can generate valuable insights into patient-reported health outcomes as the content is produced at high resolution by patients and caregivers, representing experiences that may be unavailable to most clinicians. Objective: We aim to determine the validity and effectiveness of advanced NLP approaches built to derive insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This review highlighted the significant impact of long COVID-19 symptoms on quality of life and identified that healthcare provider knowledge of long COVID-19 was a common barrier for persons with long COVID-19 to effectively access and navigate healthcare support [43]. A noted limitation of this review is that participants from all included studies were recruited through social media or online support groups, which the authors noted could enhance the bias of the convenience sample and reduce their likeness to the general population [44,45]. Considering the diversity of symptoms, the impact of previous hospitalization, and the uncertainty of appropriate long COVID-19 rehabilitation services, there is a need to explore the patient experience of COVID-19 care service navigation, including the nuances of recovery needs between those that experienced severe and mild acute COVID-19.…”
Section: Introductionmentioning
confidence: 98%
“…This review highlighted the significant impact of long COVID-19 symptoms on quality of life and identified that healthcare provider knowledge of long COVID-19 was a common barrier for persons with long COVID-19 to effectively access and navigate healthcare support [43]. A noted limitation of this review is that participants from all included studies were recruited through social media or online support groups, which the authors noted could enhance the bias of the convenience sample and reduce their likeness to the general population [44,45]. Considering the diversity of symptoms, the impact of previous hospitalization, and the uncertainty of appropriate long COVID-19 rehabilitation services, there is a need to explore the patient experience of COVID-19 care service navigation, including the nuances of recovery needs between those that experienced severe and mild acute COVID-19.…”
Section: Introductionmentioning
confidence: 98%